(untitled) (Razão e Fé, 2021)
The method Ver-Julgar-Agir emerged as an attempt by Joseph Cardjin to respond to the harsh reality in which the workers of his city, especially the young people, were inserted. Cardjin noticed that the church is far from the reality of the workers, so much so that when he was a seminarian and returned to his parents’ house during the vacation, he realized that, although he was the same age as his friends, he felt displaced from that social context. In order to face this desire, in the mid 1920’s, Priest Cardjin organized groups of young workers, inspired by his own methodology. A few decades later, on the Latin American continent, the desire to produce a theological reflection less dependent on European schemes and with the face and smell of the people on this ground emerged: a practical theology. Named Liberation Theology, this system incorporated the method Ver-Julgar- Agir, transforming itself into an epistemic set.